The Ability of Nuclease-Resistant RNA Aptamer against Streptococcus suis Serotype 2, Strain P1/7 to Reduce Biofilm Formation In Vitro - Apinyapat Matchawong (2022)
Streptococcus suis, a Gram-positive bacterium, is an important swine and human pathogen, with serotype 2 being the most prevalent strain found worldwide. Deafness, meningitis, and death (in severe cases) are observed in S. suis-infected cases. Development of the ligands that can bind to S. suis with high affinity and specificity could be beneficial for the diagnosis and treatment of S. suis infection. Herein, the nuclease-resistant RNA aptamers based on 2′-fluoropyrimidine modification against S. suis serotype 2, strain P1/7, were established using the cell-Systematic Evolution of Ligands by Exponential enrichment (SELEX) technique. One of the aptamers, R8-su12, could bind to the S. suis target strain as well as other S. suis serotypes, i.e., 1, 1/2, 9, and 14, but not to other bacteria tested, i.e., S. pneumoniae ATCC 49619, Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, and Pseudomonas aeruginosa ATCC 27853. Moreover, the R8-su12 RNA aptamer was also capable of inhibiting the biofilm formation of the S. suis target strain, making it potentially useful for the study of biofilm formation and the treatment of S. suis infection in humans and pigs in the future.